Dampak Sistem Administrasi Perpajakan Modern Terhadap Kepatuhan Wajib Pajak Pada Kantor Pelayanan Pajak (KPP) Madya Makassar - Rinaldy, Syiar; Ruslan (Insan Cita Bongaya Research Journal, 2021)
Taxes are the main source of state revenue, so efforts to improve taxpayer compliance are important. The purpose of this research is to measure and analyze the effect of modern tax administration system on taxpayer compliance. The research population is the number of taxpayers registered at the Makassar Madya Tax Service Office. The sampling technique used is simple random sampling. The number of samples is 100 taxpayers. Data collected by questionnaire technique. The data analysis technique used simple regression analysis. The results showed that the modern tax administration system has a significant positive effect on taxpayer compliance.